A sociologist learns to study religion - Marti, Gerardo (Critical research on religion, 2016)
It took a very long time before I encountered the systematic study of religious processes and dynamics as a distinctive and expansive area of scholarship. Using an autobiographical account, I trace the development of my scholarship in the social scientific study of religion. I have now experienced a great diversity of approaches to the study of religion. Driven by insatiable curiosity and knowing that no one can capture religion comprehensively, I now am committed to stimulating imaginative, rigorous, and wide-ranging developments in religious scholarship. We require new, inventive, and even incompatible approaches to our study of religion if we ever hope to try adequately grasping the richness of religion.